Cerebral white matter diffusion properties and free‐water with obstructive sleep apnea severity in older adults. Issue 10 (13th March 2020) - Baril, Andrée‐Ann; Gagnon, Katia; Descoteaux, Maxime; Bedetti, Christophe; Chami, Sirin; Sanchez, Erlan; Montplaisir, Jacques; De Beaumont, Louis; Gilbert, Danielle; Poirier, Judes; Pelleieux, Sandra; Osorio, Ricardo S.; et al.
Abstract: Characterizing the effects of obstructive sleep apnea (OSA) on the aging brain could be key in our understanding of neurodegeneration in this population. Our objective was to assess white matter properties in newly diagnosed and untreated adults with mild to severe OSA. Sixty‐five adults aged 55 to 85 were recruited and divided into three groups: control (apnea‐hypopnea index ≤5/hr; n = 18; 65.2 ± 7.2 years old), mild (>5 to ≤15 hr; n = 27; 64.2 ± 5.3 years old) and moderate to severe OSA (>15/hr; n = 20; 65.2 ± 5.5 years old). Diffusion tensor imaging metrics (fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity, and mean diffusivity) were compared between groups with Tract‐Based Spatial Statistics within the white matter skeleton created by the technique. Groups were also compared for white matter hyperintensities volume and the free‐water (FW) fraction. Compared with controls, mild OSA participants showed widespread areas of lower diffusivity ( p < .05 corrected) and lower FW fraction ( p < .05). Participants with moderate to severe OSA showed lower AD in the corpus callosum compared with controls ( p < .05 corrected). No between‐group differences were observed for FA or white matter hyperintensities. Lower white matter diffusivity metrics is especially marked in mild OSA, suggesting that even the milder form may lead to detrimental outcomes. In moderate to severe OSA, competing pathological responses might have led to partial normalization of diffusion metrics.